DISEÑO Y PRUEBA PILOTO DE UN SOFTWARE PARA LA MEDIDA DE AGUDEZA VISUAL DINÁMICA. - Cuenca Hoyos, Valentina; Arandia Cañón, Ingrid Tatiana; Medrano Muñoz, Sandra Milena (Science & Technology in Ocular Health & Vision / Ciencia y Tecnología para la Salud Visual y Ocular)
The article focuses on the design and pilot testing of software to measure dynamic visual acuity (DVA) in children aged 6 to 12 years in Bogotá, Colombia. DVA is crucial for assessing the functionality of the visual system, especially in moving situations, but it has been little studied in the pediatric population due to the lack of appropriate tools. A prototype was developed that simulates everyday conditions, and a pilot test was conducted with ten children, where it was observed that the difficulty in identifying stimuli increased with speed and decreased with contrast. The results suggest that the software could be a useful tool in pediatric optometry for assessing DVA.